THE IMPORTANCE OF EDUCATION TO REDUCE SELF-DESTRUCTIVE NAIL HABITS - Upeniece, Ilze; Beltiņa, Monta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Onychophagia and onychotillomania are rarely seen in clinical practice and are considered undervalued. The study aims were to determine the prevalence of onychophagia and onychotillomania habit in the patient group with hand nail damage and control group, to determine which would be the target population to educate. Patients were interviewed about self-destructive habits. Excel and SPSS were used for data analysis. In the nail damage group, 28.6% of the respondents showed self-destructive habits and past habits – 31.4%. In the control group, the result was 22.9% and 31.4%. For 74.3% of patients the cause of nail damage was skin disease (including 61.54% of respondents with nail damage who have psoriasis), for 5.7% it was age-related nail changes, for 20% traumatic damage and for 57.14% of them it was a result of self-destructive habit. In the nail damage group both – present and past self-destructive habits are higher than in the control group, but it has no statistical significance (p=0.785). 1)The prevalence of onychophagia and onychotillomania does not differ between patients and control group. 2)General education of the population is necessary to actualize this problem, which can worsen nail changes.